High-strength wear-resistant polyester fiber and preparation method thereof
By mixing modified PET, nano-masterbatch and micron-masterbatch, combined with three-stage stretching and heat setting processes, the contradiction between the mechanical strength and wear resistance of polyester fibers is resolved, achieving a synergistic improvement in high strength and wear resistance, making it suitable for clothing, home textiles and industrial fields.
Patent Information
- Application Number
- CN202510833873.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-20
- Publication Date
- 2025-09-16
- Estimated Expiration
- 2045-06-20
AI Technical Summary
Existing polyester fibers have a contradiction in improving mechanical strength and wear resistance. Single modification or filler addition makes it difficult to take into account both interface compatibility and dispersion uniformity, resulting in insufficient overall performance and affecting service life.
By mixing modified PET, nano masterbatch and micron masterbatch, combining three-stage stretching and heat setting processes, introducing end-hydroxyl polydimethylsiloxane, graphene and multi-walled carbon nanotubes, a micron-nano dual-scale reinforcement system is formed, which synergistically improves the mechanical properties and wear resistance of the fiber.
It achieves a balance between the high strength and wear resistance of polyester fiber, improves the fiber's breaking strength, elongation, heat resistance and wear resistance, and is suitable for clothing, home textiles and industrial fields.
Smart Images

Figure CN120649184A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyester fibers, in particular to a high-strength wear-resistant polyester fiber and a preparation method thereof. Background Art
[0002] Polyester is an important variety of synthetic fiber and the trade name of polyester fiber. It is a fiber-forming polymer made from terephthalic acid or dimethyl terephthalate and ethylene glycol through esterification or ester exchange and polycondensation reaction, and then made into fiber through spinning and post-processing. Polyester fiber is widely used in textile and industrial fields due to its high strength and easy processing, but there is often a contradiction between its mechanical strength and wear resistance.
[0003] Traditional polyester fibers have low elongation at break due to the strong rigidity and high crystallinity of the PET molecular chain, and their wear resistance depends on the surface coating, which poses a risk of coating peeling. Existing technologies improve toughness through copolymerization modification or the addition of inorganic fillers, but the two have poor synergy, and it is difficult to balance the interface compatibility and dispersion uniformity of the rigid reinforcement phase and the flexible toughening phase, resulting in a limited range of applications for polyester fibers. In existing technologies, simply increasing the crystallinity can enhance strength, but it will lead to excessive rigidity of the molecular chain, a decrease in elongation at break, and stress concentration during friction, causing wear; while introducing flexible segments to improve toughness may reduce high-temperature stability and load-bearing capacity. In some studies, the single addition of micron-sized glass fibers can provide rigid support, but interface defects can easily cause fracture; using only nanofillers can lead to stress concentration due to uneven dispersion, making it difficult to achieve a balance between strength and wear resistance.
[0004] In summary, existing technologies improve flexibility through copolymerization, but inevitably sacrifice strength and thermal stability. Filler additions improve overall fiber strength, but interfacial compatibility issues reduce fiber wear resistance. This focus on improving a single performance factor neglects the coordinated optimization of multiple properties. Consequently, in practice, the challenge remains of balancing mechanical strength and wear resistance, resulting in insufficient overall performance and reduced service life.
[0005] Therefore, a high-strength and wear-resistant polyester fiber and a preparation method thereof are proposed. Summary of the Invention
[0006] The purpose of the present invention is to provide a high-strength, wear-resistant polyester fiber and a preparation method thereof. Modified PET is obtained by esterification and polycondensation of terephthalic acid, ethylene glycol, terminal hydroxyl polydimethylsiloxane, and isophthalic acid; graphene and multi-walled carbon nanotubes are oxidized separately and then grafted with polyetheramine; nano masterbatch is then melt-blended with PET chips to obtain a nano masterbatch; short glass fibers and PET chips are melt-blended to prepare a micron masterbatch; the modified PET, nano masterbatch, and micron masterbatch are mixed, ultrasonically dispersed, and then an auxiliary agent is added. The high-strength, wear-resistant polyester fiber is obtained by melt spinning, three-stage stretching, and three-stage heat setting. Through the synergistic effect of the components and processes, the obtained fiber has excellent mechanical properties and wear resistance, and has broad application prospects in the fields of clothing, home textiles, and industry.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] The present invention provides a method for preparing high-strength wear-resistant polyester fiber, and the polyester fiber preparation comprises the following steps:
[0009] The modified PET is added to a high-speed mixer, and the nano masterbatch and the micro masterbatch are added in sequence, and the mixture is heated and stirred to obtain a mixture; an auxiliary agent is added to the mixture to obtain a mixed material; the mixed material is melt-spun and cooled to obtain nascent fibers; the nascent fibers are subjected to three-stage heat stretching and three-stage heat setting treatments, and then cooled and wound to obtain polyester fibers;
[0010] The modified PET is obtained by esterification and polycondensation of terephthalic acid, ethylene glycol, hydroxy-terminated polydimethylsiloxane and isophthalic acid;
[0011] Nano masterbatch is obtained by melt extrusion of nano filler and PET chips;
[0012] The nanofiller is obtained by grafting graphene oxide and carbon oxide nanotubes with polyetheramine;
[0013] Micron masterbatch is obtained by melt extrusion of chopped glass fiber and PET chips.
[0014] Preferably, the auxiliary agent includes polyethylene terephthalate grafted maleic anhydride copolymer, antioxidant 1010, perfluoropolyether and polytetrafluoroethylene powder.
[0015] Preferably, the preparation of modified PET comprises the following steps:
[0016] Terephthalic acid, ethylene glycol, hydroxyl-terminated polydimethylsiloxane and isophthalic acid are added in a vacuum dryer to obtain dry raw materials; the dry raw materials are added to a high-speed stirrer, heated and stirred to obtain a mixed system; the mixed system is added to a reactor, tetrabutyl titanate and triphenyl phosphite are added, and an esterification reaction is carried out under nitrogen protection to obtain an esterified oligomer; the esterified oligomer is transferred to a polycondensation reactor for polycondensation reaction; the material is discharged under nitrogen pressure, pelletized underwater, and vacuum dried to obtain modified PET; the modified PET has an intrinsic viscosity of 0.65-0.75 dL / g; and the average molecular weight of the hydroxyl-terminated polydimethylsiloxane is 1500-2500.
[0017] Preferably, the molar ratio of terephthalic acid to ethylene glycol is 1:1.2-1.5, the molar ratio of terminal hydroxyl polydimethylsiloxane to terephthalic acid is 0.03-0.05:1; the molar ratio of isophthalic acid to terephthalic acid is 0.1-0.3:1; tetrabutyl titanate is 0.05-0.1% by mass of terephthalic acid; and triphenyl phosphite is 0.1-0.2% by mass of terephthalic acid.
[0018] Preferably, the preparation of the nano masterbatch comprises the following steps:
[0019] 8-15 parts by mass of nanofiller, 5 parts of polyethylene terephthalate grafted maleic anhydride copolymer and 75-90 parts of PET chips are added into a co-rotating twin-screw extruder for melt blending, and a combination of strong dispersion and weak shearing is adopted, followed by vacuum exhaust; the nano masterbatch is then obtained by water-cooling, drawing, pelletizing and drying.
[0020] Preferably, the temperature of the feeding section is 250-260°C; the temperature of the compression section is 270-275°C; the temperature of the metering section is 270-285°C; the temperature of the die head is 260-270°C, the speed is controlled at 300-500rpm, and the residence time is 8-10min.
[0021] Preferably, during the melt spinning process, the spinning speed is controlled at 1200 m / min, a three-leaf hollow spinneret is used, the spinneret aperture is 0.3 mm, the aspect ratio is 1:5, the cooling air temperature is 20°C, the wind speed is 1.5 m / s, and the cooling air humidity is controlled at 30%-40%, and the nascent fiber is obtained by cooling.
[0022] Preferably, the three-stage heat stretching method includes: low temperature stage temperature of 80-90°C, stretching ratio of 1.5-2.0; medium temperature stage temperature of 100-120°C, stretching ratio of 1.8-2.5; high temperature stage temperature of 120-130°C, stretching ratio of 1.2-1.5;
[0023] The three-stage heat setting treatment includes: the first stage temperature is 180-190°C, the residence time is 20s; the second stage temperature is 200-210°C, the residence time is 15s; the third stage temperature is 220-230°C, the residence time is 10s.
[0024] Preferably, the preparation of the nanofiller comprises the following steps:
[0025] The method comprises the following steps: dispersing graphene in deionized water, ultrasonically treating the solution to obtain an ultrasonic solution, washing the solution with deionized water three times to neutrality by the Hummer method, and vacuum drying the solution at 80°C for 5 hours to obtain graphene oxide, wherein the purity thereof should be greater than 95% and the particle size should be less than 1 μm; adding multi-walled carbon nanotubes to a mixed solvent of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, oxidizing the solution at 60°C for 2 hours, separating and centrifuging the solution at 6000 rpm for 20 minutes, washing the solution with deionized water five times to neutrality, and vacuum drying the solution at 100°C for 10 hours to obtain oxidized carbon nanotubes, wherein the length thereof should be uniformly within the range of 1-2 μm; adding 50 parts of graphene oxide and 50 parts of oxidized carbon nanotubes to a mortar, using zirconium oxide grinding balls, controlling the ball-to-material ratio to 5:1-10:1, and rotating at a speed of 300-500 rpm, The method comprises the steps of: ball milling for 2-4 hours to obtain a nano-mixture; dispersing the nano-mixture in anhydrous DMF, adding an excess of thionyl chloride in a mass ratio of 5:1 to the nano-mixture, reacting at 60-70° C. for 3-6 hours under nitrogen protection, and rotary evaporating the residual solvent to obtain an acyl chloride material; adding 50 parts of polyetheramine with a molecular weight of 1000-2000 to the acyl chloride material under nitrogen protection, heating the mixture to 100-120° C., and carrying out a grafting reaction for 10-15 hours to obtain a reaction system; placing the reaction system in an absorption device filled with an appropriate amount of water to absorb generated HCl gas, separating and centrifuging the reaction system, washing the reaction system alternately with deionized water and anhydrous ethanol for 5 times, and drying the reaction system at -40° C. and a vacuum degree of 10 Pa for 12 hours to obtain a nano-filler; and detecting the grafting rate thereof to be greater than 70%.
[0026] Preferably, the preparation of micron masterbatch comprises the following steps:
[0027] 20-30 parts of chopped glass fibers (3-5 mm in length), 5 parts of PET-g-MAH and 70-80 parts of PET chips are added into a co-rotating twin-screw extruder for melt blending with a residence time of 6-8 minutes. A combination of weak shear and rapid transport is adopted. The temperature of the feeding section is 245-255°C; the temperature of the compression section is 260-270°C; the temperature of the metering section is 265-275°C; the temperature of the die head is 250-260°C, and the speed is controlled at 150-250rpm. The micron masterbatch is then obtained by water-cooling, stranding, pelletizing and drying.
[0028] The present invention also provides a high-strength wear-resistant polyester fiber, which comprises modified PET, nano masterbatch, micron masterbatch, polyethylene terephthalate grafted maleic anhydride copolymer, antioxidant 1010, perfluoropolyether and polytetrafluoroethylene powder.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] 1. The present invention introduces flexible siloxane segments and isophthalic acid through copolymerization. Although the regularity of the PET molecular chain is reduced, the low glass transition temperature of the silicon-oxygen bond gives the segment mobility, alleviating the rigid brittle fracture problem of pure PET. At the same time, the siloxane segment can act as a "molecular spring" to absorb energy during the stretching process, avoiding fracture caused by stress concentration; isophthalic acid destroys the linear regularity of the PET molecular chain, inhibits the formation of large-sized crystals, and forms small grains of uniform size, making the molecular chain slip more uniform during stretching. Through the synergistic effect of the two, the mechanical properties of the polyester fiber are improved; by introducing graphene oxide and oxidized carbon nanotubes, after being grafted with polyetheramine, the surface amino groups and PET-g-M The anhydride groups of AH form covalent bonds, and the interfacial bonding strength is improved; through ultrasonic dispersion, the nanofillers are evenly distributed in the PET matrix to form a nano-reinforced network. Under the action of external force, the fiber strength is further improved through the load transfer effect and crack deflection effect. Short-cut glass fibers are added synergistically as a rigid skeleton. The glass fibers and nanofillers form a micron-nano dual-scale reinforcement system. The micron-level fibers resist macroscopic deformation, and the nanofillers inhibit microscopic cracks, which further improves the fiber strength; finally, through a three-stage stretching process, low-temperature high-magnification stretching fixes the initial orientation of the molecular chain, medium-temperature relaxation stretching forms an oriented crystalline network, and high-temperature qualitative stretching eliminates internal stress, so that the breaking strength and elongation are balanced.
[0031] 2. The present invention introduces polysiloxane, and the silicon-oxygen bond has a high bond energy. The silicon chain segment can form a "flexible thermal insulation layer" above 200°C, which hinders the conduction of heat to the PET matrix, increases the heat deformation temperature, and improves the heat resistance. The introduction of graphene and carbon nanotubes can quickly conduct local heat due to high thermal conductivity to avoid the generation of hot spots. The nanosheet layer forms a heat conduction barrier in the matrix, delaying heat diffusion and further improving the heat resistance of the fiber. In the segmented heat setting process, the low temperature conditions in the first stage promote the diffusion of molecular chains in the amorphous region to the crystalline region to form an initial crystal nucleus. The medium temperature process in the second stage promotes the rapid growth of the crystal nucleus into a complete α-crystal. The small grains dissolve and recrystallize at high temperature in the third stage to form large-sized stable crystals, with reduced crystal defects and significantly enhanced heat deformation resistance. Through the synergistic effect of components and processes, the heat resistance of the fiber is further improved, and the overall strength of the fiber is improved.
[0032] 3. The present invention introduces terminal hydroxyl polydimethylsiloxane into the modified PET matrix structure. During the processing, the siloxane is enriched on the fiber surface to form an elastic lubricating layer, which cushions the impact of abrasive particles, reduces the generation of surface microcracks during friction, and improves wear resistance. The wear resistance is further improved by synergistic use of nanofillers. The graphene sheet structure is added step by step and evenly distributed on the fiber surface to resist magic cutting. The addition of carbon nanotubes acts as a microspring to absorb friction heat and reduce friction loss. Finally, the low surface energy of PFPE and the self-lubricating core-shell structure of PTFE synergize to form a lubricating film on the fiber surface to further resist friction loss. The synergistic effect of multiple components and processes is used to form a three-dimensional wear-resistant mechanism in which the flexible matrix bears stress, the rigid filler disperses the load, and the lubricating layer reduces friction, thereby improving the overall wear resistance of the fiber. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a test chart of the heat resistance of the polyester fibers obtained in Examples 6-7, Comparative Examples 4-6, and Comparative Examples 10-12 of the present invention. DETAILED DESCRIPTION
[0034] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0035] PET-g-MAH is a polyethylene terephthalate grafted maleic anhydride copolymer.
[0036] See also Figure 1 The present invention provides a high-strength wear-resistant polyester fiber and a preparation method thereof. The technical solution is as follows:
[0037] Example 1
[0038] 500 parts of terephthalic acid, 260 parts of ethylene glycol, 600 parts of terminal hydroxyl polydimethylsiloxane and 200 parts of isophthalic acid are added to a vacuum drying oven and dried at 100°C for 2 hours to obtain a dry raw material; the dry raw material is added to a high-speed stirrer, heated to 90°C, and stirred and mixed for 45 minutes to obtain a mixed system; the mixed system is added to a reactor, 0.4 parts of tetrabutyl titanate and 0.8 parts of triphenyl phosphite are added, and under nitrogen protection, the temperature is stirred and raised to 250°C, the pressure is controlled at 0.4 MPa, and the esterification reaction is carried out for 3 hours to obtain an esterified oligomer; the esterified oligomer is transferred to a polycondensation reactor, heated to 280°C, maintained at a vacuum degree of 50 Pa, and the polycondensation reaction is carried out for 5 hours, discharged under nitrogen pressure, pelletized underwater, and vacuum dried at 100°C for 10 hours to obtain a modified PET.
[0039] Graphene was dispersed in deionized water and treated with ultrasonic power of 300W for 60min to obtain an ultrasonic solution, which was washed with deionized water 3 times to neutrality by Hummer method and dried in vacuum at 80℃ for 5h to obtain graphene oxide; multi-walled carbon nanotubes were added to a mixed solvent of concentrated sulfuric acid and concentrated nitric acid with a volume ratio of 3:1, oxidized at 60℃ for 2h, separated and centrifuged at 6000rpm for 20min, washed with deionized water 5 times to neutrality, and dried in vacuum at 100℃ for 10h to obtain oxidized carbon nanotubes; 50 parts of graphene oxide and 50 parts of oxidized carbon nanotubes were added to a mortar, and zirconium oxide grinding balls were used to control the ball-to-material ratio to 8:1 and the rotation speed was 400rpm. The nano-mixture was obtained by ball milling for 3 hours; the nano-mixture was dispersed in anhydrous DMF, and an excess of thionyl chloride was added in a mass ratio of 5:1 to the nano-mixture, and the mixture was reacted at 70°C for 4 hours under nitrogen protection, and the residual solvent was removed by rotary evaporation to obtain an acyl chloride material; 50 parts of polyetheramine was added to the acyl chloride material under nitrogen protection, the temperature was raised to 120°C, and the grafting reaction was carried out for 10 hours to obtain a reaction system; the reaction system was placed in an absorption device filled with an appropriate amount of water to absorb the generated HCl gas, and then separated and centrifuged, and washed alternately with deionized water and anhydrous ethanol for 5 times, and dried at -40°C and a vacuum degree of 10 Pa for 12 hours by a vacuum freeze-drying method to obtain a nano-filler;
[0040] 12 parts of nanofiller, 5 parts of PET-g-MAH and 85 parts of PET chips were added to a co-rotating twin-screw extruder for melt blending. The residence time was set to 10 minutes. A combination of strong dispersion and weak shear was adopted, the speed was controlled at 500 rpm, melt extrusion was carried out, and vacuum exhaust was performed. The nano masterbatch was then obtained by water cooling, stranding, pelletizing and drying.
[0041] 20 parts of chopped glass fiber, 5 parts of PET-g-MAH and 80 parts of PET chips were added to a co-rotating twin-screw extruder for melt blending with a residence time of 8 minutes. A combination of weak shear and rapid transport was used and the speed was controlled at 200 rpm. The micron masterbatch was then obtained by water-cooling, stranding, pelletizing and drying.
[0042] 90 parts of modified PET were added to a high-speed blender, and after stirring was started, 15 parts of nano masterbatch and 25 parts of micron masterbatch were added in sequence, the temperature was raised to 90° C., and stirred for 2 hours to obtain a mixture; 0.5 parts of antioxidant 1010, 6 parts of PET-g-MAH, and 6 parts of a mixture of PFPE and PTFE micropowders in a mass ratio of 2:1 were added to the mixture to obtain a mixed material; the mixed material was added to a melt spinning device, and the extrusion speed was controlled at 60 ml / h to obtain a melt; the melt was spun and cooled to obtain spun fibers;
[0043] The spun fibers are subjected to three-stage heat stretching by a stretching machine to obtain stretched fibers; the stretched fibers are added to a vacuum drying oven, subjected to three-stage heat setting treatment, and cooled and wound to obtain high-strength and wear-resistant polyester fibers.
[0044] The three-stage heat stretching method includes: low temperature stage at 80℃, stretching ratio of 1.5-2.0; medium temperature stage at 120℃, stretching ratio of 1.8-2.5; high temperature stage at 130℃, stretching ratio of 1.2-1.5;
[0045] The three-stage heat setting treatment includes: the first stage temperature is 180°C, the residence time is 20s; the second stage temperature is 205°C, the residence time is 15s; the third stage temperature is 230°C, the residence time is 10s.
[0046] Examples 2-5 refer to the preparation methods and parameter conditions of Example 1, with the differences shown in Table 1.
[0047] Table 1 Parameter changes of Examples 1-5
[0048]
[0049] Comparative Example 1 refers to Example 1, except that no hydroxyl-terminated polydimethylsiloxane is added to obtain the modified PET.
[0050] Comparative Example 2 refers to Example 1, except that no isophthalic acid is added to obtain modified PET.
[0051] Comparative Example 3 refers to Example 1, except that no modification treatment is performed during the synthesis of PET.
[0052] Comparative Example 4 refers to Example 1, except that no nano masterbatch is introduced and only micron masterbatch is used.
[0053] Comparative Example 5 refers to Example 1, except that no micron masterbatch is introduced and only nano masterbatch is used.
[0054] Comparative Example 6 refers to Example 1, except that no micron masterbatch and nano masterbatch are introduced at the same time, and the same amount of modified PET is directly melt-spun to obtain spun fibers.
[0055] Comparative Example 7 refers to Example 1, except that the three-stage stretching process is not used, and only the medium-temperature and high-temperature stages are performed.
[0056] Comparative Example 8 refers to Example 1, except that the three-stage stretching process is not used, and only the high-temperature stage is performed.
[0057] Comparative Example 9 refers to Example 1, except that high-speed stirring treatment is not performed during the preparation of the spun fibers.
[0058] Experimental Example 1 Mechanical Properties Test
[0059] The polyester fibers prepared in Examples 1-5 and Comparative Examples 1-9 were tested for breaking strength and breaking elongation according to the test method of GB / T 14344-2022. The test results are shown in Table 2.
[0060] Table 2 Test results of Examples 1-5 and Comparative Examples 1-9
[0061]
[0062]
[0063] The results in Table 2 show that, by adjusting the components and processes in the comparative examples, the obtained polyester fibers exhibit significantly lower mechanical properties compared to those in the examples, and the balance between breaking strength and breaking elongation cannot be guaranteed; in comparative examples 1-3, no hydroxy-terminated polydimethylsiloxane is added, and no silicon-oxygen bond is introduced by copolymerization, the flexibility of the molecular chain is reduced, and the rigidity of the PET molecular chain is too large, resulting in a decrease in breaking elongation; at the same time, the lubricating effect of the siloxane is lost, resulting in stress concentration inside the fiber and a decrease in breaking strength; without the introduction of isophthalic acid, the PET molecular chain has high regularity, the molecular chain rigidity is increased, and the breaking elongation is significantly reduced. However, the higher crystallinity retains the initial strength of the material, and the strength change is small; without modification, the pure PET molecular chain has strong polarity and high crystallinity, lacks flexible segments and comonomer adjustment, and the prepared fiber is hard and brittle, with significantly reduced breaking strength and elongation, lacks the synergistic effect of isophthalic acid and siloxane, and the mechanical properties are significantly reduced; the results of comparative examples 4-6 show that nanofillers can enhance the interface bonding force and evenly disperse stress; at the same time, micron-sized glass fiber provides rigid support. When only micron masterbatch is used, the stress dispersion effect of nanofillers is lacking, and the fiber is easily caused by the interface defects of micron fillers The fiber is broken, resulting in a decrease in strength and elongation; the "skeleton effect" of the glass fiber can limit the slippage of the molecular chain. Although the elongation is slightly improved after the loss, the strength loss is more significant. Nano and micro fillers achieve strength-toughness balance through synergistic effect. The nano fillers refine the grains and the addition of micro fillers bears the load. After the loss, the fiber only relies on the performance of the modified PET itself and lacks external reinforcement. The strength and elongation are reduced. The results of comparative examples 7-8 show that the three-stage stretching gradually optimizes the molecular chain arrangement through low-temperature orientation, medium-temperature refinement and high-temperature shaping. The lack of low-temperature orientation and insufficient initial orientation of the molecular chain , slippage or breakage is likely to occur during medium and high temperature stretching, resulting in a decrease in breaking strength and elongation; similarly, if the high temperature process is directly carried out, the molecular chains move violently at high temperature, and there is a lack of gradual orientation in the low and medium temperature stages, resulting in a loose internal structure of the fiber, extremely low orientation, and random breakage is likely to occur during stretching, with significantly reduced strength and elongation; in Comparative Example 9, the high-speed mechanical stirring process breaks up the nanofiller agglomerates to ensure their uniform dispersion in the PET matrix; without this process, the nanofillers are likely to agglomerate to form stress concentration points, resulting in a decrease in fiber strength. At the same time, the agglomerates hinder the slippage of the molecular chains, and the elongation at break is further reduced.
[0064] Example 6 is the same as Example 1;
[0065] Examples 7-9 refer to the preparation method parameters and conditions of Example 1, and the differences are shown in Table 3.
[0066] Table 3 Parameter changes of Examples 6-9
[0067]
[0068] Comparative Example 10 refers to Example 1, except that only graphene oxide is used to modify the nanofiller.
[0069] Comparative Example 11 refers to Example 1, except that only oxidized carbon nanotubes are used to modify the nanofiller.
[0070] Comparative Example 12 refers to Example 1, except that no polyetheramine modification treatment is used.
[0071] Comparative Example 13 refers to Example 1, except that the nanofiller is not melted through PET chips to obtain nano masterbatch, but is directly melt-blended and spun.
[0072] Comparative Example 14 refers to Example 1, except that the three-stage heat setting process is not performed, and only the second-stage setting process is performed.
[0073] Comparative Example 15 refers to Example 1, except that the three-stage heat setting process is not performed, and only the third stage setting process is performed.
[0074] Experimental Example 2 Heat Resistance Test
[0075] The polyester fibers prepared in Examples 6-9, Comparative Example 1, Comparative Examples 4-6, and Comparative Examples 10-15 were tested for initial breaking strength according to the test method of GB / T14344-2022; the polyester fibers were placed in a heat aging box, treated at 180°C for 30 minutes, cooled to room temperature, and the strength after treatment was tested. The breaking strength retention rate was calculated, and the test results are shown in Table 4; the breaking strength retention rates of the polyester fibers obtained in Examples 6-7, Comparative Examples 4-6, and Comparative Examples 10-12 are shown in Table 4. Figure 1 shown.
[0076] Table 4 Test results of Examples 6-9, Comparative Example 1, Comparative Examples 4-6, Comparative Examples 10-15
[0077]
[0078]
[0079] As shown in Table 4, the heat resistance of the polyester fiber obtained by adjusting the components and processes in the comparative example is significantly reduced compared with the embodiment; the results of comparative example 1 show that the introduction of the silicon-oxygen bond of the terminal hydroxyl polydimethylsiloxane improves the heat resistance of the main chain, and at the same time, the flexible chain segment can dissipate heat stress through molecular chain sliding, thereby avoiding the breakage of the PET molecular chain due to rigid accumulation at high temperature; when not added, the rigidity of the PET molecular chain is enhanced, the stress concentration is aggravated at high temperature, resulting in a more significant decrease in breaking strength; the results of comparative examples 4-6 show that when only micron glass fiber is used, the thermal conductivity and interface reinforcement of the nanofiller are lacking, and the thermal stress inside the fiber is concentrated at high temperature, resulting in a more obvious decrease in strength; similarly, when relying solely on nanofillers, their characteristics cannot provide sufficient high-temperature support, the molecular chain slip is aggravated, resulting in an increase in the decrease in strength and a decrease in heat resistance; nano / micro fillers conduct heat by forming a heat-conducting-enhancing network, the nanofiller conducts heat, and the micron filler bears the load. Without adding the nanofiller, the fiber relies solely on the thermal stability of the modified PET itself, and the violent movement of the molecular chain segments leads to a decrease in strength under thermal conditions. The results show that the thermal conductivity of the nanofiller decreases significantly; in Comparative Examples 10-11, when graphene oxide is used alone, the directional heat conduction path of carbon nanotubes is lacking, and heat is easily accumulated inside the fiber, resulting in a decrease in high-temperature strength; and the lack of graphene oxide leads to poor dispersion of the nanofiller, weak interface bonding, and easy detachment from the matrix at high temperatures; combined with the results of Comparative Example 12, it can be seen that polyetheramine introduces amino groups on the surface of the nanofiller through grafting reaction, forms chemical bonds with PET-g-MAH, and improves the filler-matrix interface bonding. When the grafting rate is insufficient, the nanofiller and the PET matrix are physically adsorbed. The interface is easily debonded at high temperature, resulting in an increase in the strength reduction; in Comparative Example 13, direct blending easily leads to filler agglomeration and forms stress defects. The generation of agglomerates becomes a source of thermal stress concentration at high temperature, further causing fiber breakage; in Comparative Examples 14-15, the lack of the first section leads to the failure to eliminate the initial internal stress, and the molecular chain slips due to stress relaxation at high temperature, aggravating the strength reduction; the lack of the first section and the gradual crystallization optimization of the second section results in the formation of coarse grains inside the fiber, which are prone to grain boundary sliding at high temperature, resulting in a significant decrease in strength.
[0080] Example 10 is the same as Example 1;
[0081] Examples 11-14 refer to the preparation method and parameter conditions of Example 1, with the differences shown in Table 5.
[0082] Table 5 Parameter changes of Examples 10-14
[0083]
[0084]
[0085] Comparative Example 16 refers to Example 1, except that the nanofiller is not melted through the PET chips to obtain the nano masterbatch, and the chopped glass fiber is not melted through the PET chips to obtain the micron masterbatch. The nanofiller, chopped glass fiber and modified PET are directly melt-spun to obtain the spun fiber.
[0086] Comparative Example 17 refers to Example 1, except that no lubricant is added.
[0087] Comparative Example 18 refers to Example 1, except that an equal amount of PFPE is used as the lubricant instead of PTFE micropowder.
[0088] Comparative Example 19 refers to Example 1, except that PFPE is not used as the lubricant, but an equal amount of PTFE powder is used.
[0089] Experimental Example 3 Wear resistance test
[0090] The polyester fibers prepared in Examples 10-14, Comparative Example 1, Comparative Example 4-6, Comparative Example 13, and Comparative Examples 16-19 were tested according to the GB / T 21196.1-2007 test method. The wear resistance of the fibers was reflected by the number of abrasions, mass loss, and appearance change under a load of 12 kPa. The test results are shown in Table 6.
[0091] Table 6 Test results of Examples 10-14, Comparative Example 1, Comparative Examples 4-6, Comparative Example 13, Comparative Examples 16-19
[0092]
[0093]
[0094] From the results in Table 6, it can be seen that the wear resistance of the polyester fiber obtained by adjusting the components and processes in the comparative example is significantly reduced compared with the embodiment; the results of comparative example 1 show that the low glass transition temperature of the silicon-oxygen bond enables the molecular chain to relieve friction stress by slipping. After the loss, the rigid PET chain is easily broken due to stress concentration, resulting in wear loss during the friction process; in addition, siloxane can improve the interfacial bonding between PET and fillers. After the loss, the glass fiber and nanofiller are easily detached from the matrix; in comparative examples 4-6, there is a lack of nanofillers to fill the gaps, and the wear is concentrated around the glass fiber. The resulting micron-level gaps cause the glass fiber to detach during the friction process, resulting in reduced wear resistance; lacking the "physical barrier" of micron glass fibers, the PET matrix is excessively deformed during friction, resulting in internal tearing, and the number of wear times decreases; although the hydrogen bonds between the PET molecular chains provide a certain strength, the lack of external fillers to share the friction load causes wear to act directly on the matrix, resulting in premature appearance of holes and a significant reduction in wear resistance; in comparative example 13, direct blending causes graphene oxide and carbon nanotubes to form micron-level agglomerates, which become "hard" during friction In Comparative Example 16, the nanofiller agglomerates interact with the glass fiber agglomerates during the preparation process, forming a wear chain reaction, which significantly reduces the wear times. At the same time, the edges of the glass fiber agglomerates cut the PET matrix, and the nanoagglomerates fall off to form grooves, which appear as matrix tearing and fiber flake shedding. In Comparative Examples 17-19, the PET surface roughness is high. In the absence of lubricant, the friction work is directly converted into heat energy, resulting in fiber melt adhesion wear, which is visible as severe scratches and exposed fibers. The addition of lubricant can migrate to the surface during friction to form a lubricating film, further improving the wear resistance of the fiber. Without the hard points formed by PTFE to resist abrasives, the PET debris generated by friction will aggravate internal wear. However, the high surface energy of single PTFE leads to a dynamic imbalance between interfacial adhesion and friction on the contact surface, aggravating fiber surface fatigue fracture.
[0095] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing high-strength wear-resistant polyester fiber, characterized in that: The polyester fiber preparation comprises the following steps: The modified PET is added to a high-speed mixer, and the nano masterbatch and the micro masterbatch are added in sequence, and the mixture is heated and stirred to obtain a mixture; an auxiliary agent is added to the mixture to obtain a mixed material; the mixed material is melt-spun and cooled to obtain spun fibers; the spun fibers are subjected to three-stage heat stretching and three-stage heat setting treatments, and then cooled and wound to obtain the polyester fiber; The modified PET is obtained by esterification and polycondensation of terephthalic acid, ethylene glycol, terminal hydroxyl polydimethylsiloxane and isophthalic acid; The nano masterbatch is obtained by melt extrusion of nano filler and PET chips; The nanofiller is obtained by grafting graphene oxide and carbon oxide nanotubes with polyetheramine; The micron masterbatch is obtained by melt-extruding chopped glass fibers and PET chips.
2. The method for preparing high-strength wear-resistant polyester fiber according to claim 1, characterized in that: The auxiliary agent comprises polyethylene terephthalate grafted maleic anhydride copolymer, antioxidant 1010, perfluoropolyether and polytetrafluoroethylene powder.
3. The method for preparing high-strength wear-resistant polyester fiber according to claim 1, characterized in that: The preparation of the modified PET comprises the following steps: The terephthalic acid, the ethylene glycol, the hydroxy-terminated polydimethylsiloxane, and the isophthalic acid are added to a vacuum dryer to obtain a dry raw material; the dry raw material is added to a high-speed stirrer, and the temperature is increased and stirred to obtain a mixed system; the mixed system is added to a reactor, tetrabutyl titanate and triphenyl phosphite are added, and an esterification reaction is carried out under nitrogen protection to obtain an esterified oligomer; the esterified oligomer is transferred to a polycondensation reactor for polycondensation reaction; The modified PET is obtained by discharging the material under nitrogen pressure, pelletizing the material underwater, and vacuum drying.
4. The method for preparing high-strength wear-resistant polyester fiber according to claim 1, characterized in that: The preparation of the nano masterbatch comprises the following steps: The nano filler, polyethylene terephthalate grafted maleic anhydride copolymer and the PET chips are added into a co-rotating twin-screw extruder for melt blending, and a combination of strong dispersion and weak shearing is adopted, followed by vacuum exhaust; the nano masterbatch is then obtained by water cooling, drawing, pelletizing and drying.
5. The method for preparing high-strength wear-resistant polyester fiber according to claim 4, characterized in that: The preparation of the nanofiller comprises the following steps: The method comprises the following steps: dispersing graphene in deionized water, ultrasonically treating the graphene, washing the deionized water prepared by the Hummer method until the water is neutral, and vacuum drying to obtain graphene oxide; adding multi-walled carbon nanotubes to a mixed solvent of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, performing oxidation treatment, separating and centrifuging, washing the mixed solvent with deionized water, and vacuum drying to obtain oxidized carbon nanotubes; ball milling the graphene oxide and the oxidized carbon nanotubes to obtain a nano-mixture; dispersing the nano-mixture in anhydrous DMF, adding an excess of thionyl chloride, and reacting the mixed solvent to obtain an acyl chloride material; adding polyetheramine to the acyl chloride material, carrying out a graft reaction to obtain a reaction system; separating and centrifuging the reaction system, washing the mixed solvent with deionized water and anhydrous ethanol alternately, and vacuum freeze-drying the mixed solvent to obtain the nano-filler.
6. The method for preparing high-strength wear-resistant polyester fiber according to claim 1, characterized in that: The preparation of the micron masterbatch comprises the following steps: The chopped glass fibers, PET-g-MAH and PET chips are added to a co-rotating twin-screw extruder for melt blending, using a combination of weak shearing and rapid transport; and then the micron masterbatch is obtained by water-cooling, stranding, pelletizing and drying.
7. A high-strength, wear-resistant polyester fiber prepared by the method of claim 1, characterized in that: The polyester fiber comprises modified PET, nano masterbatch, micron masterbatch, polyethylene terephthalate grafted maleic anhydride copolymer, antioxidant 1010, perfluoropolyether and polytetrafluoroethylene powder.
Citation Information
Patent Citations
Polyetheramine-modified graphene oxide and epoxy composite nano-material thereof
CN109897227A
Heat-conducting plastic master batch, preparation method thereof and heat-conducting plastic
CN110172166A
Preparation method of graphene and liquid crystal polyester synergistically-enhanced polymer fibers
CN110184678A
Preparation method of super-smooth and soft polyester staple fibers
CN117468116A
Method for preparing hybrid material from recycled PET textile fiber and inorganic micro-nano composite powder as well as product and application thereof
CN118459948A
Cited By
High-toughness polyester and preparation method thereof
CN121183448A
Preparation process of graphene reinforced porous hollow polyester fiber
CN121228393A
Preparation process of graphene reinforced porous hollow polyester fiber
CN121228393B
Method for reducing PET melt spinning pressure on premise of low damage to fiber performance
CN121272573A
Production method of strong yarn pulling rope
CN121700698A